2xy-3y+6=0

Simple and best practice solution for 2xy-3y+6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2xy-3y+6=0 equation:


Simplifying
2xy + -3y + 6 = 0

Reorder the terms:
6 + 2xy + -3y = 0

Solving
6 + 2xy + -3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + 2xy + -6 + -3y = 0 + -6

Reorder the terms:
6 + -6 + 2xy + -3y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 2xy + -3y = 0 + -6
2xy + -3y = 0 + -6

Combine like terms: 0 + -6 = -6
2xy + -3y = -6

Add '3y' to each side of the equation.
2xy + -3y + 3y = -6 + 3y

Combine like terms: -3y + 3y = 0
2xy + 0 = -6 + 3y
2xy = -6 + 3y

Divide each side by '2y'.
x = -3y-1 + 1.5

Simplifying
x = -3y-1 + 1.5

Reorder the terms:
x = 1.5 + -3y-1

See similar equations:

| 3x-5=24+7 | | (3x-18)=105+99 | | 5.4+-9.7= | | 2/3x-1/2=3/4 | | 29n=-377 | | 2(x+3)=4*-3 | | (2x-4)2=36 | | 4(6x-31)=5-4(x+3) | | 7(4x+8)-6=-106 | | 3v^2+12v=-8 | | 7x-4=-2x+2+9x-5 | | 9(x+1)=25+6 | | -2(2-x)=-8+6x | | 11+2n=9 | | -7(1x-6)=-14 | | 57=5x-3 | | -3(5m+4)-3(m-7)= | | y-12=89 | | 5x^2+11xy+2y^2=0 | | mx=-nx+p | | 9x-15=9(x-13) | | 38=8+6(y+2) | | 136=-17b | | -27.083x-11.246-16.819= | | f(x)=-27.083x-11.246-16.819 | | -2+y=4x+9 | | k^2+2k-75=5 | | 13-6a+2a=5-6a | | 28=k/5 | | 4x^2-0.2x+0.01=0 | | 8[m+5]=16 | | x+5+1=x |

Equations solver categories